Does Islamic insurance development promote economic growth? a panel data analysis - Muye, Ibrahim Muhammad; Sheikh Hassan, Ahmad Fahmi (Elsevier, 2016)
This paper examines the impact of Islamic insurance development on economic growth. The Islamic insurance market has been experiencing tremendous growth in its activities since inception, particularly in the ASEAN and GCC markets. Using the difference GMM estimation technique for dynamic panel data model for a set of 22 countries for the period 2004 to 2012, we find a strong evidence of a positive and significant effect from the Islamic insurance activities on economic growth. We further find a robust positive and significant link between trade and economic growth, a positive but insignificant relationship between CPI and economic growth while government consumption show a negative relation. Our result provides further support for the supply-leading hypothesis in the finance growth literature.